2016
DOI: 10.1007/s10570-016-0943-9
|View full text |Cite
|
Sign up to set email alerts
|

Application of nanocomposite cellulose fibers with luminescent properties to paper functionalization

Abstract: Cellulose fibres modified with the luminescent inorganic compound were obtained by using N-methylmorpholine-N-oxide as a direct solvent. The fibres were cut and introduced to the unrefined and refined paper pulp samples. Schopper-Riegler value of the pulps were measured and the laboratory paper samples were formed. Observations under UV radiation showed that the cellulose luminescent fibres were randomly and even scattered in the paper and were well visible. Measurements of the paper properties such as tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This method can create cellulose fibers with unique properties, such as electrically conductive, luminescent, and antibacterial properties, among others. Research by Erdman et al (2016) showed that cellulose fibers functionalized in this way are very resistant to mechanical impacts and aging factors. It was found that even in the case of mechanical damage of the fiber structure, the substance used for its functionalization remained in the structure and did not release into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…This method can create cellulose fibers with unique properties, such as electrically conductive, luminescent, and antibacterial properties, among others. Research by Erdman et al (2016) showed that cellulose fibers functionalized in this way are very resistant to mechanical impacts and aging factors. It was found that even in the case of mechanical damage of the fiber structure, the substance used for its functionalization remained in the structure and did not release into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Erdman et al (Erdman et al, 2016) investigated the application of monowavelength excitable fluorescent Lyocell fibers modified with cerium fluoride that had been doped with terbium particles (Ce 0.85 Tb 0.15 F 3 ) to paper functionalization. They showed that there were no significant changes in either measured structural or strength properties upon introduction of monowavelength excitable fluorescent Lyocell fibers to the paper.…”
Section: Introductionmentioning
confidence: 99%
“…cellulose. 37 This means lyocell fibres could have better binding properties. These properties can be further increased by fibre fibrillation during the refining process.…”
Section: Introductionmentioning
confidence: 99%